Interleukin-6: Molecule in the Intersection of Cancer, Ageing and COVID-19 - Brábek, Jan; Jakubek, Milan; Vellieux, Fréderic; Novotný, Jiří; Kolář, Michal; Lacina, Lukáš; Szabo, Pavol; Strnadová, Karolína; Rösel, Daniel; Dvořánková, Barbora; Smetana, Karel (International journal of molecular sciences, 2020)
Interleukin-6 (IL-6) is a cytokine with multifaceted effects playing a remarkable role in the initiation of the immune response. The increased level of this cytokine in the elderly seems to be associated with the chronic inflammatory setting of the microenvironment in aged individuals. IL-6 also represents one of the main signals in communication between cancer cells and their non-malignant neighbours within the tumour niche. IL-6 also participates in the development of a premetastatic niche and in the adjustment of the metabolism in terminal-stage patients suffering from a malignant disease. IL-6 is a fundamental factor of the cytokine storm in patients with severe COVID-19, where it is responsible for the fatal outcome of the disease. A better understanding of the role of IL-6 under physiological as well as pathological conditions and the preparation of new strategies for the therapeutic control of the IL-6 axis may help to manage the problems associated with the elderly, cancer, and serious viral infections.
Keywords: pandemie; Aging; Pandemics; cancer ecosystem; Signal Transduction; cytokine; Interleukin-6; cytokine storm; Humans; koronavirové infekce; IL-6; lidé; COVID-19; virová pneumonie; ageing; nádory; interleukin-6; signální transdukce; Animals; cancer-associated fibroblasts; zvířata; tumour microenvironment; Coronavirus Infections; stárnutí; Neoplasms; Pneumonia, Viral